When Companies Do Good, Are Their Products Good for You? How Corporate Social Responsibility Creates a Health Halo. (April 2015) - Peloza, John; Ye, Christine; Montford, William J.
Research has demonstrated that consumers frequently engage in inference making when evaluating food products. These inferences can be highly inaccurate, leading to unintended, unhealthy consumer choices. Previous research has examined the role of inference making in consumption settings from either an inter- or intra-attribute perspective. The current research highlights extra-attribute inferences, in which consumers use corporate-level information to make inferences about product-level attributes. Across four studies, the authors demonstrate the existence of a health halo resulting from corporate social responsibility activities. When consumers evaluate food products marketed by firms with strong corporate social responsibility reputations, they underestimate the calorie content. Furthermore, the authors show that this calorie underestimation can lead to overconsumption by consumers.